Multiferroic CoFe2O4-Pb(Zr0.53Ti0.47)O3 thick films for magnetoelectric application - Chen, Wei (2012)
Recent theoretical breakthroughs in understanding the concurrence of magnetic and electrical ordering, combined with advances in thin film growth techniques and experimental methods for observing magnetic and electric domains, have generated a flurry of research activity on magnetoelectric (ME) multiferroics [1, 2]. Theoretical studies have shown that the usual atomic-level mechanisms driving ferromagnetism and ferroelectricity are mutually exclusive, because they require partially and empty filled transition metal orbitals, respectively [3]. This recognition has prompted a search for alternative ferroelectric mechanisms that are compatible with the occurrence of magnetic ordering. As a result, previously unknown multiferroic materials have been discovered. In the past few years, combining ferromagnetism and ferroelectricity in one material and coupling between ferromagnetism and ferroelectricity were two big challenges in multiferroics. With the developments in magnetoelectricity (ME) theory and the renovation of deposit technique, multiferroic CoFe2O4-Pb(Zr0.53Ti0.47)O3 (CFO-PZT) system is experiencing a renaissance recently due to its attractive ME effect and potential applications in multifunctional devices. However, much attention has been paid on CFO-PZT thin films and their bulk ceramics. The exploration on multiferroic thick films was nearly being on vacuum, which severely restricted the development of multiferroic materials on micro-electro-mechanical systems (MEMS) applications. In the present thesis, we are aiming to investigate the CFO-PZT thick films comprehensively, especially focusing on their ME coupling development, so as to find their possible applications on MEMS devices. A series of works along this direction are hence presented as three main parts in this thesis. Screen printing method has been attempted to fabricate CFO-PZT composite thick films. This is a simple and cost-saving method which has been widely applied in industry and research lab. With this method, CFO-PZT composite thick films were fabricated on alumina substrate at a low sintering temperature with thicknesses up to hundreds of micrometers. The ferromagnetic and ferroelectric properties of these thick films were characterized. However, the porosities of these thick films degraded severely their ferroelectric properties and lowered the potential ME coupling effect. Hence, we had to develop another method to prepare CFO-PZT composite thick films. A hybrid sol-gel processing has been developed to deposit CFO-PZT composite thick film. This method inherently has advantages in making biphasic nanocomposites which exhibit concurrent ferromagnetic and ferroelectric properties. Before preparing the CFO-PZT composite thick films, pure CFO thick films realized by this method are studied in the second part, which includes the preparation of nano-sized CFO particles, synthesis of CFO sol-gel solution, and proper combining of CFO nanoparticles and sol-gel solution for uniform CFO slurry as well as the deposit tips by spin coating technique. 10 µm of cobalt ferrite composite thick films were deposited on platinum covered silicon wafers via this hybrid sol-gel processing. Phase structures revealed a critical annealing temperature above which the pure spinel phase was obtained. The measurement of magnetization versus magnetic field demonstrated a saturated magnetization and coercive magnetic field comparable to those of a CFO thin film deposited by other chemical or physical techniques. A more interesting phenomenon was observed in their impedance spectra, where a dielectric relaxation behavior, similar to those noticed in manganese and nickel ferrites bulk materials, had been studied through frequency and temperature dependence of impedance spectra, electrical modulus, dielectric spectra and AC conductivity spectra. Ion motion and jump mechanism in cobalt ferrite thick films were investigated and discussed in detail. The last part presents the preparation of CFO-PZT multiferroic composite thick films, including their fully characterizations, mechanisms analysis, consistent optimization and applications evaluation. A hybrid sol-gel process was adopted to deposit CFO-PZT composite thick films. Thick films in the desired thickness range (3~5 µm), along with a concurrence of ferromagnetic and ferroelectric properties, were achieved. Subsequently, we studied the effect of polyvinylpyrrolidone (PVP) on microstructures, ferromagnetic, and ferroelectric properties of CFO-PZT composite thick films. It was observed that PVP benefited to enhance the film thickness remarkably and avoid the cracks probably induced by different thermal expansion coefficients or lattice mismatch between different materials. However, the disadvantage of PVP was that it diluted the ferroelectric properties and reduced the ME coefficients of the composite thick films. To deal with this issue, PZT sol infiltration was introduced to enhance the ferroelectric and dielectric properties of the composite thick films. It was found that enough sol infiltration between slurry layers dramatically improves the densification of the microstructure as well as the ferroelectric and dielectric properties. Through further combining PVP and sol infiltration, ferromagnetic properties were also promoted. With a dense microstructure and enhanced ferroelectric and ferromagnetic properties, a strong ME effect was expected in CFO-PZT composite thick films. Furthermore, dielectric studies of CFO-PZT thick films were conducted in detail. Dielectric relaxation was observed in multiferroic system and its physical mechanism was investigated.